The Concept of Civilization in Scientific, Ideological and Everyday Discursive Practices of Wartime in Ukraine - Kononov, Illya (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2018)
The article analyzes the concept of «civilization» in the context of the modern sociological language. It is shown that at the moment this concept has the lack of clarity of its content. Its history has led to the preservation in it the idea of linear progress with its characteristic steps and idea of different cultural areas. The dialectical tension between universalism and particularism in the concept of civilization has not yet become a stimulus for the development of the theory of civilization. The scientific program of the civilization approach is interdisciplinary and philosophical discourse prevails in it. The hard core of the program demonstrates the inability to development. The history of the study of civilizations is a series of author’s visions of reality. There is no repeatability of the results and no falsification of the fundamental thesis of the civilizational approach. The peripheral moments of scientific program of the civilization approach vary depending on the political predilections of scientists and specific circumstances. Most of the forecasts made by supporters of the civilizational approach have not been confirmed in the course of historical development. Insufficient sociological elaboration of the concept of civilization makes it unproductive in scientific research and in public practice. At moments of international crises and wars the civilizational approach turns into a translator of ideological influences on sociology. This is demonstrated by the basic texts of Nikolai Danilevsky and Samuel Huntington. In the geopolitics of large countries, the civilizational approach justifies their right to dominate in some part of the globe. Elites of small countries use it to substantiate the choice of an external patron and to join certain unions. In Ukraine, at present, the civilizational approach is mainly used in the options of civilizational war and civilizational choice. As empirical studies show, it does not find support in the mass consciousness and can not serve the purposes of mobilizing the population to confront the enemy.